2001
DOI: 10.1038/88213
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have carried out automated extraction of explicit and implicit biomedical knowledge from publicly available gene and text databases to create a gene-to-gene co-citation network for 13,712 named human genes by automated analysis of titles and abstracts in over 10 million MEDLINE records. The associations between genes have been annotated by linking genes to terms from the medical subject heading (MeSH) index and terms from the gene ontology (GO) database. The extracted database and accompanying web tools for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
124
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(124 citation statements)
references
References 22 publications
0
124
0
Order By: Relevance
“…In addition to these high-throughput techniques, another interesting tactic is to aggregate the results of individual experiments through comprehensive literature searches. Although there clearly are difficulties with differing experimental conditions and varying interpretations, preliminary results have shown this to be an effective method (Jenssen et al 2001;Marcotte et al 2001;Ono et al 2001). …”
Section: (Epstein and Butow 2000)mentioning
confidence: 99%
“…In addition to these high-throughput techniques, another interesting tactic is to aggregate the results of individual experiments through comprehensive literature searches. Although there clearly are difficulties with differing experimental conditions and varying interpretations, preliminary results have shown this to be an effective method (Jenssen et al 2001;Marcotte et al 2001;Ono et al 2001). …”
Section: (Epstein and Butow 2000)mentioning
confidence: 99%
“…We used PubGene web tools to identify groups of genes that had co-occurred in the literature and whose expression pattern may shed light on signaling pathways and critical effectors of these genes (Jenssen et al, 2001). Recently, it has been demonstrated that gene pairs with network neighborhoods occurring more frequently together in article abstracts can be functionally related.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the biological relationship between the 109 differentially expressed genes and to identify coexpressed groups of genes associated in the literature, we used PubGene web tools (http://www.pubgene.org/ tools/Network/Subset.cgi) (Jenssen et al, 2001). We identified 40 genes which co-occurred in the literature with at least one other gene of the CT8-ps (Figure 4).…”
Section: Functional Profiling Of Differentially Expressed Genesmentioning
confidence: 99%
“…Natural language processing or text mining tools like PubGene [171], iHOP [172], CoPubMapper [173], or the Agilent Literature Search tool [174] can be used to automatically scan the scientific literature in order to identify co-occurrence of genes and proteins. However, manual checking of interactions derived on this level is mandatory; otherwise the number of false positive interactions will be high.…”
Section: Regulatory Context Analysismentioning
confidence: 99%